2016
DOI: 10.1016/j.semcdb.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Contextual signaling in cancer

Abstract: The formation and maintenance of an organism is highly dependent on the orderly control of cell growth, differentiation, death, and migration. These processes are tightly regulated by signaling cascades in which a limited number of molecules dictate these cellular events. While these signaling pathways are highly conserved across species and cell types, the functional outcomes that result from their engagement are specified by the context in which they are activated. Using the Neurofibromatosis type-1 (NF1) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The deficiencies in the knowledge and the complexity of the mechanisms sustaining tumour growth are well known to the investigators and are also clearly mentioned in the updated article by Hanahan & Weinberg (2011). In a recent review (Smithson et al 2016), it has been suggested that 'signalling represents the language of the cell, where molecules (words) and cellular context (syntax) serve as units of informational content'; in addition, the authors stated that 'when we study signalling pathways in normal cells or in the setting of cancer, we often fail to consider how the cellular language conferred by these pathways is influenced by context, that is, the different extracellular signals present in the immediate milieu, the various adaptive responses that limit and promote intracellular signal transduction, the innate properties of distinct cell types responding to these cues, and the impact of epigenetic/genomic changes on the ultimate consequence of these informational signals'. They concluded that 'a deeper appreciation of contextual signalling may improve our understanding of the basic principles that govern development'.…”
Section: Incomplete Knowledge Of the Mechanisms And The 'Contextual Smentioning
confidence: 99%
“…The deficiencies in the knowledge and the complexity of the mechanisms sustaining tumour growth are well known to the investigators and are also clearly mentioned in the updated article by Hanahan & Weinberg (2011). In a recent review (Smithson et al 2016), it has been suggested that 'signalling represents the language of the cell, where molecules (words) and cellular context (syntax) serve as units of informational content'; in addition, the authors stated that 'when we study signalling pathways in normal cells or in the setting of cancer, we often fail to consider how the cellular language conferred by these pathways is influenced by context, that is, the different extracellular signals present in the immediate milieu, the various adaptive responses that limit and promote intracellular signal transduction, the innate properties of distinct cell types responding to these cues, and the impact of epigenetic/genomic changes on the ultimate consequence of these informational signals'. They concluded that 'a deeper appreciation of contextual signalling may improve our understanding of the basic principles that govern development'.…”
Section: Incomplete Knowledge Of the Mechanisms And The 'Contextual Smentioning
confidence: 99%
“…Our short summary and the papers of this special issue [25,29,30,33,36,39,42,52,57] highlight the promises and challenges of using signaling networks (including RAS-related signaling events) in the description of cancer initiation and development, metastasis and the emergence of drug resistance. As key messages we emphasize that…”
Section: Discussionmentioning
confidence: 99%
“…The approaches outlined above and in the contributions of this special issue [25,29,30,33,36,39,42,52,57] may overcome the current Nietzschean dilemma of cancer cell targeting: “what does not kill me makes me stronger” [60]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations